Factores asociados a mala evolución de crisis asmática en niños de 5 a 14 años de edad en el Hospital Regional Docente de Trujillo durante el periodo 2018 - Blas Rivera, Patricia Bettsy (2019)
Objective: To determine the factors associated with poor therapeutic response of acute asthma in children 5 to 14 years at the Regional Hospital of Trujillo during 2018. Materials and Methods: A descriptive cross-sectional study. A questionnaire to parents of children aged 5 to 14 years with poor therapeutic response of acute asthma. The statistical significance is carried out by means of a nonparametric test of the independence criteria using the Square distribution with a significance level of 5%. Results: Cases of acute asthma remains one of the most frequent reasons for consultation. In our country we have found prevalences in Emergency up to 20%. The patient with asthma may present certain conditions that are not identified that condition a poor clinical course and that make it difficult to control the disease despite adequate treatment. Therefore, it is necessary to recognize in our environment the factors that condition a bad evolution of the acute asthma to be able to prevent them, mainly the modifiable factors. And in this way contribute to the reduction of the hospitalization rate.